A single-dose of stellate ganglion block for the prevention of postoperative dysrhythmias in patients undergoing thoracoscopic surgery for cancer: A randomised controlled double-blind trial. Issue 4 (April 2020) - Wu, Cai-Neng; Wu, Xin-Hai; Yu, Dong-Nan; Ma, Wu-Hua; Shen, Chun-Hui; Cao, Ying
Abstract : BACKGROUND: New-onset arrhythmias and sleep disturbances are frequently observed during the postoperative period in patients undergoing thoracic surgery. OBJECTIVE: We evaluated the effectiveness of a single-dose stellate ganglion block (SGB) to prevent the occurrence of arrhythmias in patients undergoing thoracic surgery for cancer. DESIGN: Randomised controlled double-blind study. SETTING: Single university hospital. PATIENTS: Ninety patients with lung cancer or oesophagal cancer scheduled for elective video-assisted thoracoscopic surgery were randomly randomised into one of two equal groups (the SGB group and control group, n = 40 each). INTERVENTIONS: Patients received a single dose of 5 ml of 0.5% ropivacaine during ultrasound-guided SGB before induction of general anaesthesia in the SGB group. MAIN OUTCOME MEASURES: Holter ECG was continuously monitored during the first 48 postoperative hours, and sleep state was monitored during the first two postoperative nights. RESULTS: The incidences of postoperative supraventricular tachycardias were lower in the SGB group compared with the control group during the first 48 postoperative hours; 11.6 (5/43) vs. 31.8% (14/44), respectively, P = 0.023 (odds ratio 0.28, 95% confidence interval 0.09 to 0.87). The SGB also prolonged the total sleep time and increased the sleep efficiency during the first two postoperative nights. The duration of stage N2 sleep was longer in the SGB group compared with the control group [28 (interquartile range, 14 to 58) to 94 (interquartile range, 69 to 113) min, P = 0.016] on the first postoperative night. There were no differences in the duration of stage N1 and N3 sleep ( P = 0.180, 0.086, respectively) on the first postoperative night, and the duration of stage N1, N2 and N3 sleep ( P = 0.194, 0.057, 0.405, respectively) on the second postoperative night between the groups. CONCLUSION: A pre-operative SGB effectively prevented the occurrence of postoperative supraventricular tachycardias and improves the objective sleep quality in patients undergoing thoracic surgery for cancer. TRIAL REGISTRATION NUMBER: ChiCTR-1900023064.